VIBRATIONAL PROCESSES OF HEMODYNAMICS IN ASSESSMENT OF THE CONDITION OF GRAVIDARIUM HOMEOSTASIS - Бухтоярова, Валентина Ивановна; Артымук, Дмитрий Анатольевич (Mother and Baby in Kuzbass, 2017)
The aim of the study – to evaluate the possibility of determining the heart rate variability for assessing the state of the mother and fetus.Materials and methods. The information bases of the system Cochrane, Medline, PubMed, E-library were estimated. Key words for search: heart rate variability fetus and mothers, gravity homeostasis.Results of the study. 692 publications have been found. The review shows that studies of heart rate variability are widely conducted in such areas of medicine as neurology, endocrinology, oncology. Heart rate variability has been studied in physiological pregnancy and physical exercise in healthy pregnant women, hypertensive disorders, nutritional deficiencies, premature birth, infected pregnancy and other complications.Conclusion. The results of a review of Russian and foreign literature have shown that the study of the variability of the heart rate of the mother and fetus can be widely used to assess of the gravidar homeostasis in physiological and pathological pregnancies.
Keywords: heart rate variability fetus and mothers; gravity homeostasis